VALIDATION STUDY OF STEROIDAL DRUGS (DEXAMETHASONE AND BETAMETHASONE) BY U.V. SPECTROPHOTOMETRIC METHOD - Anand, Khilav; Pandey, Astha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present investigation involves development and validation of ultraviolet (UV) spectroscopic method for estimation of dexamethasone and betamethasone in a pharmaceutical dosage as per International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) guidelines. Method: Betamethasone and dexamethasone were dissolved in 50 mL Methanol: water (1:2) and 50 mL distilled water, respectively. The method was validated for accuracy, precision, linearity, ruggedness, and robustness to check its consistency. Result: The λmax or the absorption maxima of both the drugs was found to be 241 nm. A linear response was observed in the range of 10–20 μg/mL. Conclusion: The method could be applied for the analysis of marketed tablets and also can be used for the routine analysis of dexamethasone and betamethasone in bulk formulations using UV method. It is suitable for the intended purpose especially in forensic science laboratories and other laboratories involved in the pharmaceutical analysis.